Recuperación de oro de minerales auríferos refractarios, la importancia de la caracterización mineralógica y el efecto del oxígeno en la lixiviación ácida - Gutarra Bernaola, Alcides Renán (2023)
Acid leaching is a processing alternative to improve the recovery of gold from gold ores made up of pyrite and arsenopyrite called refractory minerals, the gold contained in this type of ore is hardly soluble by conventional processes, the mineral investigated is the tailings of a process of direct cyanidation, it has a law of 0.14 Oz/TC; the mineralogical characterization carried out on this mineral shows that the gold particles are less than 5 microns and that it is associated with arsenopyrite and pyrite; both species represent 46.30 % of the total volume.The acid solution is composed of 0.1 M sulfuric acid, 0.4 M potassium nitrate and 0.6 M sodium chloride, sulfuric acid (H2SO4) reacts with potassium nitrate (KNO3) to form nitric acid (HNO3) and it reacts with sodium chloride (NaCl) to form nitrosyl chloride, which is a component of aqua regia, (NOCl) the latter is a powerful gold leach; the recovery achieved is 28.74%, adding enriched oxygen to 90% purity, a recovery of 37.08% of gold is achieved.